1998
DOI: 10.1038/sj.bjp.0701808
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y‐induced potentiation of noradrenergic vasoconstriction in the human saphenous vein: involvement of endothelium generated thromboxane

Abstract: 1 We investigated the potentiating e ect of low concentrations of neuropeptide Y (NPY) on the vasoconstriction induced by transmural nerve stimulation (TNS) and noradrenaline (NA) in human saphenous veins. The e ects of (i) endothelium removal; (ii) the addition of the NO pathway precursor L-arginine; (iii) the ET A /ET B endothelin receptor antagonist Ro 47-0203; (iv) the cyclo-oxygenase inhibitor, indomethacin; (v) the selective thromboxane A 2 (TxA 2 ) receptor antagonists Bay u3405 and ifetroban, and (vi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…The endothelium is known to produce vasoconstrictors such as endothelin-1 (ET-1) and prostaglandins [10, 18, 19, 20]. Accordingly the possible contributions of these two compounds to abnormal vasoconstriction of the diabetic tissue have been tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelium is known to produce vasoconstrictors such as endothelin-1 (ET-1) and prostaglandins [10, 18, 19, 20]. Accordingly the possible contributions of these two compounds to abnormal vasoconstriction of the diabetic tissue have been tested.…”
Section: Resultsmentioning
confidence: 99%
“…Prostaglandin synthesis is usually ascribed to the endothelium [10, 19, 20], which is not directly stimulated by PE. Data were previously shown, however, indicating that the alpha-adrenergic activated contractile response could be mediated by the endothelium-dependent vascular production of ET-1 [7]or angiotensin [36].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects and in animals, NPY via Y1 receptors acts as a vasoconstrictor, potentiating the effects of other like agents, such as NE and ANG II (4,19,21). In heart failure, NPY's vasoconstrictive properties were found to be attenuated and the natriuretic/afterload reducing actions enhanced (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the vasoconstriction induced by stimulation of some receptors can be enhanced, or even uncovered, by increasing tone through Gq protein-coupled receptor pathway (Choppin and O'Connor, 1995;Movahedi and Purdy, 1997). Several studies have shown that the vasoconstriction induced by ␣-AR stimulation can be potentiated by agonists of other G protein-coupled receptors (Fabi et al, 1998;Bhattacharya and Roberts, 2003). Different mechanisms are proposed to explain this kind of potentiation, like tyrosine kinase/protein kinase Cdependent pathway (Henrion and Laher, 1994), a RhoA/Rho kinase pathway (Boer et al, 2002), or the extracellular signal-regulated kinase/mitogen-activated protein kinase cascade (Bhattacharya and Roberts, 2003).…”
mentioning
confidence: 99%